Cytokines as villains and potential therapeutic targets in thyroid-associated ophthalmopathy: from bench to bedside. (June 2014) - Rajaii, Fatemeh; McCoy, Allison N; Smith, Terry J
<x xml:space="preserve">Abstract</x> The pathophysiology underlying Graves' disease and its ocular manifestation, thyroid associated ophthalmopathy (TAO) is not completely understood. Characterization of the mononuclear cells driving the disease and the cytokines they produce has led to significant advances in our understanding of TAO. This in turn has resulted in the identification of potentially attractive drug targets. For instance, development of specific cytokine pathway inhibitors for use in other autoimmune diseases now presents an opportunity for their application in TAO. In this paper, the authors review the rationale for considering anti-cytokine therapy in TAO, evidence linking specific cytokines such as IL-6, TNF-α, and IL-17 pathways to TAO, and explore the potential of targeting these pathways for therapy.